Del ser para la muerte al ser contra la muerte. Una reconsideración del vitalismo hiperbólico de Emmanuel Lévinas (2010)
We start whith a critical review of the canonical interpretation of the Platonic theme of caring for the one’s own death as a condition typical of the philosopher: the Phaedo does not propose something like a “preparation for death”, but rather an intensely reflective soul resistance against the natural process of death. We understand that the heterologicphenomenology of Lévinas enables to formalize this hyperbolic vitalism Platonic roots through the category of “being against the death” in systematic controversy with Heidegger famous “being for death” from Lévinas allows a philosophical understanding of the natural “fear of death” of all living things: the permanent “stalling” in the last hour gives time and opportunity to a desire of the Other, unthinkable though in the coordinates of Heidegger’s Existential solipsism.Keywords: “Being toward death”, “be against thedeath”, “postponement”.